The age of shadows [videorecording (DVD)] - Kim, Chi-un, 1964-; Burden, Foster (CJ Entertainment, 2016)
Set in the late 1920s, the story follows a cat-and-mouse game between a group of resistance fighters who want to destroy key Japanese facilities in Seoul, and the Japanese agents trying to stop them. A talented Korean-born Japanese police officer, who was previously in the independence movement himself, is torn between his duty as an officer and his instinct to support the greater cause.